Northern Ireland and truth and reconciliation healing through remembering: The story so far - Wall David (Temida)
This paper outlines the work of truth and reconciliation project done in Northern Ireland "Healing through Remembering", and the findings of the Project Group that reported in June 2002. The Paper identifies future actions emerging from the Report.